mRNA splicing-mediated C-terminal replacement of transcription factor Hac1p is required for efficient activation of the unfolded protein response - Mori, Kazutoshi (The National Academy of Sciences, 2000)
Eukaryotic cells control the levels of molecular chaperones and folding enzymes in the endoplasmic reticulum (ER) by a transcriptional induction process termed the unfolded protein response (UPR) according to the needs within the ER. In Saccharomyces cerevisiae, expression of the UPR-specific transcription factor Hac1p is tightly regulated at the level of mRNA splicing that depends on an unconventional system. Thus, HAC1 precursor mRNA is constitutively expressed but not translated. A sensor molecule Ire1p/Ern1p-mediated signaling from the ER specifically removes an intron of 252 nucleotides from the precursor mRNA, and the resulting mature mRNA is translated to produce Hac1p. Because the 5′ splice site is located near the C-terminal end of the Hac1p-coding region, this splicing replaces the last 10 codons of the ORF with an exon encoding 18 aa without affecting the N-terminal 220-aa region which contains the DNA-binding domain. Here, we found that this C-terminal 18-aa segment functions as a potent activation domain. Therefore, the splicing event joins the HAC1 DNA-binding domain to its activation domain, allowing rapid posttranscriptional generation of a potent transcriptional activator (238-aa Hac1p) that activates the UPR efficiently. This suggests that the UPR is hardly activated by Hac1p produced without splicing (230-aa Hac1p) which may occur in the absence of Ire1p/Ern1p-mediated signaling from the ER. Based on these and other results, we propose that the control of expression and activity of Hac1p meets the requirements of the ER.